Long Run Sustainability Of Sarawak - West Kalimantan Cross-Border Trade Flows - Nurul, Bariyah; Lau, Evan; Shazali, Abu Mansor (Ebscohost, 2012)
This paper is concerned with the time series behaviour of the cross border trade flows Sarawak (East Malaysia) - West Kalimantan (Indonesia) conducted through regional Tebedu custom district with the main focus on the long run sustainability of Sarawak trade Cross border trade activity has gain much attention due to the dynamic linkages of this regional economic activity on industry, investment and employment, yet the study on relationships of cross border trade flows have been largely overlooked. By employing stages of modern time series econometric technique, the research found significant cointegration relationship for the bilateral trade flows as well as support for the strong sustainability condition, suggesting that Sarawak-West Kalimantan bilateral trade sustainable path in governing their trade flows performance. This suggests that the macroeconomic policies of Sarawak and West Kalimantan have been effective in bringing exports and imports a long run equilibr